2016
DOI: 10.1002/gps.4424
|View full text |Cite
|
Sign up to set email alerts
|

Is integrated care associated with service costs and admission rates to institutional settings? An observational study of community mental health teams for older people in England

Abstract: ObjectivesTo evaluate the association between the degree of integration in community mental health teams (CMHTs) and: (i) the costs of service provision; (ii) rates of mental health inpatient and care home admission.MethodsAn observational study of service use and admissions to institutional care was undertaken for a prospectively‐sampled cohort of patients from eight CMHTs in England. Teams were chosen to represent ‘high’ or ‘low’ levels of integrated working practice and patients were followed‐up for seven m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…This study indicated that respondents' likelihood to recommend the service increased when there were more disciplines involved in their care. This appears to support the model of effective multidisciplinary working as being well placed to meet the needs of individuals and promote good patient experience, perhaps linked to the potential to arrange more care and resources overall …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This study indicated that respondents' likelihood to recommend the service increased when there were more disciplines involved in their care. This appears to support the model of effective multidisciplinary working as being well placed to meet the needs of individuals and promote good patient experience, perhaps linked to the potential to arrange more care and resources overall …”
Section: Discussionmentioning
confidence: 76%
“…This appears to support the model of effective multidisciplinary working as being well placed to meet the needs of individuals and promote good patient experience, perhaps linked to the potential to arrange more care and resources overall. 32 The second finding challenges the generally accepted and longstanding view that patient evaluations of care quality increase with age. 33 This research finds the opposite with a general decline in reported quality amongst the oldest age groups.…”
Section: Discussionmentioning
confidence: 98%
“…An observational study comparing patients supported by integrated and non-integrated CMHTs identified that integration was associated with the delivery of more intensive and wide-ranging community support, but no evidence could be found that patient outcomes were otherwise improved. 47 A robust evidence base to support efforts towards integrated care remains elusive. Nevertheless, it is cited as a policy goal and activity across jurisdictions.…”
Section: Organisation and Working Practicementioning
confidence: 99%
“…In the UK, integrated teams of professionals in a range of health‐care and social care disciplines work to reduce inpatient and care home admission . In contrast, most patients with dementia in Japan periodically attend clinics or hospitals after their initial diagnosis, mainly for prescriptions, and are cared for within social care services at other times.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, integrated teams of professionals in a range of health-care and social care disciplines work Home-visit nursing for BPSD © 2018 Japanese Psychogeriatric Society to reduce inpatient and care home admission. 16 In contrast, most patients with dementia in Japan periodically attend clinics or hospitals after their initial diagnosis, mainly for prescriptions, and are cared for within social care services at other times. A care manager can liaise closely with social care providers but not with hospital-based care systems, and it is on this point that home-visit nursing is likely to bridge the various care systems and enable collaborative activities that enhance support for the patient's independent life at home (Fig.…”
Section: Discussionmentioning
confidence: 99%